Preparation method of europium-antimony-niobium-Fe-site co-doped nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material

The regeneration of waste lithium iron phosphate positive electrode material through europium antimony niobium Fe-position co-doping and nitrogen-doped carbon coating technology has solved the problems of low recycling efficiency and poor material performance in the prior art, and achieved high conductivity, excellent rate performance and good cycle stability.

CN119725836APending Publication Date: 2025-03-28CHONGQING YUANDA CATALYST MFG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411902458.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art has problems of low recycling efficiency, high energy consumption and environmental pollution in the recycling process of waste LiFePO4 positive electrode materials, and the materials prepared by traditional high-temperature solid phase methods have poor conductivity and high-rate performance.

Method used

The preparation method of the modified regenerated waste lithium iron phosphate positive electrode material is adopted by the europium antimony niobium Fe-position co-doping and nitrogen-doping carbon coating, and the uniform doping coating of the material is achieved through plasma ball milling and nitrogen plasma bombardment technology.

Benefits of technology

It improves the conductivity and rate performance of the material, enhances cycle stability, reduces the cost of recycling used batteries, and is simple and easy to promote.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725836A_ABST
    Figure CN119725836A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a europium-antimony-niobium-Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material, which comprises the following steps: discharging a waste lithium iron phosphate battery, separating out a positive electrode plate, carrying out ultrasonic drying to obtain waste lithium iron phosphate positive electrode powder, putting the waste lithium iron phosphate positive electrode powder into a 500 DEG C argon atmosphere tube furnace, and carrying out pretreatment to obtain the europium-antimony-niobium-Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material. The obtained waste lithium iron phosphate positive electrode powder, a lithium source, an iron source, a europium source, an antimony source, a niobium source and a phosphorus source are mixed according to the molar ratio of 1: (1-x-y-z): x: y: z: 1, x is equal to 0.01-0.05, y is equal to 0.005-0.03, z is equal to 0.005-0.05, and the mixture is transferred into nitrogen for plasma ball milling. And roasting the mixed precursor in a tubular furnace to finally obtain the europium-antimony-niobium-Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material. The regenerated lithium iron phosphate positive electrode material obtained by the invention is uniform in particle, high in conductivity, excellent in rate capability and good in cycling stability. The method is simple in process and easy to popularize and apply.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium iron phosphate positive electrode materials, and specifically relates to a preparation method of europium, antimony, niobium, Fe-position co-doped and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material. Background Art

[0002] Lithium iron phosphate (LiFePO4) batteries are widely used in electric vehicles and other fields due to their excellent cycle performance, environmental friendliness, and high safety factor. However, as lithium-ion batteries face retirement due to capacity decay after 3 to 5 years of use, the recycling and remanufacturing of waste lithium batteries has become a key link in achieving the sustainable development of the lithium-ion battery industry. This is not only related to the effective utilization of resources, but also closely linked to environmental protection, and has far-reaching strategic significance. At present, the main methods for recycling waste LiFePO4 positive electrode materials are pyrometallurgy and hydrometallurgy. However, the low recovery efficiency, high energy consumption and harmful gas emissions in the pyrometallurgical process have jointly limited the widespread application of pyrometallurgy in the field of waste battery recycling; although hydrometallurgical technology provides a different recycling path, acid and alkali leaching agents must be used in the process, which not only complicates the process flow, but also may cause serious environmental pollution, thus hindering the sustainable development of the battery recycling industry.

[0003] Recently, direct regeneration technology has received extensive attention. Direct regeneration technology includes hydrothermal method, high temperature solid phase method, electrochemical method, etc. Although the direct regeneration method can achieve targeted repair of spent LiFePO4 positive electrode without damaging the LiFePO4 olivine crystal structure, for example, the hydrothermal method requires high temperature and high pressure operation, which has certain risks and uneven material mixing; and the conductivity and high rate performance of materials prepared by the traditional high temperature solid phase method are still poor.

[0004] In view of the above problems, the present invention aims to provide a method for preparing a regenerated lithium iron phosphate positive electrode material with simple operation, high conductivity, excellent rate performance and good cycle stability. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a europium, antimony, niobium, Fe-position co-doped and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material.

[0006] The object of the present invention is achieved by providing a method for preparing a modified recycled waste lithium iron phosphate positive electrode material by co-doping europium, antimony, niobium and Fe and nitrogen-doped carbon coating, wherein the chemical expression of the recycled waste lithium iron phosphate positive electrode material is LiFe 1-x-y-z Eu x Sb y Nb zPO4@NC; the molar ratio of lithium, iron, europium, antimony, niobium and phosphorus is 1:1-xyz: x:y:z:1, where x=0.01~0.05, y=0.005~0.03, z=0.005~0.05; The preparation method of the regenerated waste lithium iron phosphate positive electrode material is achieved by the following steps: 1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, which is placed in a 500°C argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; 2) mixing the obtained waste lithium iron phosphate positive electrode powder, lithium source, iron source, phosphorus source, europium source, antimony source and niobium source, transferring the mixture to a plasma ball mill, and performing plasma ball milling in nitrogen to obtain a mixed precursor; 3) The mixed precursor is placed in a tube furnace and calcined to finally obtain a europium, antimony, niobium, Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material.

[0007] The present invention uses a plasma ball milling method, and the high-energy particles generated can improve the surface activity of the material. The obtained positive electrode material has the advantages of fine powder particle size and uniform particle distribution. The doping and coating regeneration of waste lithium iron phosphate positive electrode materials can be achieved in a relatively short time, which greatly reduces the cost of regeneration of waste batteries. Europium, antimony and niobium are co-doped on the Fe position. Among them, europium doping can change the electronic structure of the material in the lithium iron phosphate battery, adjust the distribution of electronic energy levels, make electrons more easily transition, and thus improve the conductivity and reaction activity of the positive electrode. After antimony is added to the lithium iron phosphate positive electrode material, it can effectively inhibit the performance degradation of the battery material caused by structural changes during the charging and discharging process, and extend the service life of the battery. Niobium doping can extend the Li-O bond, change the lattice parameters, and reduce the binding energy between lithium atoms and oxygen atoms. This structural change helps the rapid diffusion of lithium ions in the battery material, thereby achieving faster charging and discharging speeds. The present invention combines the advantages of three elements, europium, antimony and niobium, to achieve co-doping, which can synergistically change the electronic structure and band structure of lithium iron phosphate battery materials, improve the conductivity of lithium iron phosphate, and increase the unit cell volume of lithium iron phosphate battery materials, providing more channels for the migration of lithium ions, further promoting the transmission of lithium ions, thereby improving the electrochemical performance and service life of the battery. Nitrogen plasma is used to bombard the carbon layer on the surface of waste lithium iron phosphate to construct a nitrogen-doped carbon coating layer, which further improves the conductivity of the material, accelerates the transmission of lithium ions and electrons, and effectively alleviates the erosion of the electrolyte on the lithium iron phosphate positive electrode material.

[0008] The preparation method of the present invention uses nitrogen plasma to bombard the waste lithium iron phosphate carbon layer to construct a nitrogen-doped carbon coating layer, and combines the ball milling method to achieve uniform co-doping of europium, antimony, niobium and Fe positions, and the obtained regenerated lithium iron phosphate positive electrode material has uniform particles, high conductivity, excellent rate performance and good cycle stability. The method of the present invention is simple in process and easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 The XRD spectrum of the recycled lithium iron phosphate positive electrode material co-doped with europium, antimony, niobium and Fe and modified by nitrogen-doped carbon coating is shown in the example; Figure 2 a and b are respectively SEM images of the waste lithium iron phosphate and europium antimony niobium Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode materials of Example 1; Figure 3 This is a graph of the cycle performance of the waste lithium iron phosphate and europium antimony niobium Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material at 1 C rate in Example 1; Figure 4 The cycle performance diagram of the waste lithium iron phosphate and europium antimony niobium Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material of Example 1 at 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C and 10 C rates; Figure 5 The XRD spectrum of the recycled lithium iron phosphate positive electrode material co-doped with europium antimony niobium Fe and nitrogen-doped carbon coating is shown in Example 2; Figure 6 This is a graph of the cycling performance of the Eu-Sb-Nb Fe-co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material at 1C rate in Example 2; Figure 7 The XRD spectrum of the recycled lithium iron phosphate positive electrode material co-doped with europium antimony niobium Fe and nitrogen-doped carbon coating is shown in Example 3; Figure 8 This is a graph of the cycling performance of the Europium, Antimony, and Niobium Fe-coated and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material at 1C rate in Example 3; Fig. 9 This is a graph of the cycling performance of the modified regenerated lithium iron phosphate positive electrode material co-doped with europium, antimony and niobium at the Fe position in comparative example 1 at a 1 C rate; Fig.10 This is the cycling performance diagram of the modified regenerated lithium iron phosphate positive electrode material co-doped with europium and antimony at the Fe site in comparative example 2 at a rate of 1 C.

[0010] Fig.11 This is a graph of the cycling performance of the europium-doped modified regenerated lithium iron phosphate positive electrode material of comparative example 3 at a 1 C rate. DETAILED DESCRIPTION

[0011] The technical solution of the present invention will be further described in detail below in combination with the embodiments of the present invention and the accompanying drawings. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0012] The present invention discloses a method for preparing a Europium, Antimony, Niobium, Fe-coated and nitrogen-doped carbon-coated modified recycled waste lithium iron phosphate positive electrode material, wherein the chemical expression of the recycled waste lithium iron phosphate positive electrode material is LiFe 1-x-y-z Eu x Sb y Nb z PO4@NC; the molar ratio of lithium, iron, europium, antimony, niobium and phosphorus is 1:1-xyz: x:y:z:1, where x=0.01~0.05, y=0.005~0.03, z=0.005~0.05; The preparation method of the regenerated waste lithium iron phosphate positive electrode material is achieved by the following steps: 1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, which is placed in a 500°C argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; 2) mixing the obtained waste lithium iron phosphate positive electrode powder, lithium source, iron source, phosphorus source, europium source, antimony source and niobium source, transferring the mixture to a plasma ball mill, and performing plasma ball milling in nitrogen to obtain a mixed precursor; 3) The mixed precursor is placed in a tube furnace and calcined to finally obtain a europium, antimony, niobium, Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material.

[0013] In step 2), the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium acetate, and lithium oxalate.

[0014] In step 2), the iron source is one or more of ferric oxide, ferric acetate, ferric nitrate, ferrous sulfate, and ferrous oxalate.

[0015] In step 2), the phosphorus source is one or more of lithium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate.

[0016] In step 2), the europium source is one or more of europium nitrate, europium oxalate, europium acetate, and europium phosphate.

[0017] In step 2), the antimony source is one or more of antimony pentoxide, antimony acetate, and antimony trichloride.

[0018] In step 2), the niobium source is one or more of niobium oxide, niobium oxalate and niobium hydroxide.

[0019] In step 2), the plasma ball milling time is 30-180 min, the ball milling speed is 900-1300 r / min, the discharge frequency is 5-10 KHz, and the ball-to-material ratio is 5-30:1.

[0020] In step 3), argon or nitrogen is used as the inert gas in the tubular furnace for calcination, the heating rate of the tubular furnace is 2-10°C / min, the calcination temperature is 500-750°C, and the holding time is 3-6 h.

[0021] Example 1 A preparation method of europium, antimony, niobium, Fe-coated and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material, the specific steps are as follows: (1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, and is placed in a 500° C. argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; (2) The obtained waste lithium iron phosphate positive electrode powder, lithium carbonate, ferric acetate, europium nitrate, antimony acetate, niobium hydroxide and ammonium dihydrogen phosphate were mixed in a molar ratio of 1:0.97:0.01:0.01:0.01:1, transferred to a plasma ball mill, and plasma ball milled in nitrogen to obtain a mixed precursor. The ball milling time was 60 min, the ball milling speed was 1300 r / min, the discharge frequency was 10 kHz, and the ball-to-material ratio was 10:1.

[0022] (3) The mixed precursor was placed in an argon tube furnace and calcined at a heating rate of 5°C / min, a calcination temperature of 700°C, and a treatment time of 6 h. Finally, the Eu-Sb-Nb Fe-co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material (LiFe 0.97 Eu 0.01 Sb 0.01 Nb 0.01 PO4@NC). Figure 1 It can be seen that SLFP has FePO4 impurity peaks, while LiFe 0.97 Eu 0.01 Sb 0.01 Nb 0.01 The PO4@NC material is consistent with the standard diffraction peak of lithium iron phosphate (PDF#81-1173), indicating that the crystal structure of waste lithium iron phosphate has been repaired and doping has no effect on the crystal structure of lithium iron phosphate. Compared with the waste lithium iron phosphate positive electrode material (serious agglomeration phenomenon), the regenerated lithium iron phosphate positive electrode material is more dispersed and the particle size is reduced, which helps to shorten the lithium ion diffusion path and increase the high-rate discharge performance of lithium iron phosphate ( Figure 2 ).

[0023] Figure 3 For SLFP and LiFe 0.97 Eu 0.01 Sb 0.01 Nb 0.01 The cycling performance diagram of PO4@NC material at 1 C current density shows that the initial discharge capacity of SLFP is 104.7 mAh g -1 The capacity retention rate after 200 cycles is 83.6%. 0.97 Eu 0.01 Sb 0.01 Nb 0.01 The initial discharge capacity of PO4@NC is 159.1 mAh g -1 The capacity retention rate is 99.8% after 200 cycles, indicating that the co-doping of Eu, Sb, Nb at the Fe site and the nitrogen-doped carbon coating improve the electrochemical performance of lithium iron phosphate.

[0024] Figure 4 For SLFP and LiFe 0.97 Eu 0.01 Sb 0.01 Nb 0.01 The rate performance diagram of PO4@NC material. It can be seen that SLFP has poor rate performance, especially at 10 C rate, there is almost no capacity. 0.97 Eu 0.01 Sb 0.01 Nb 0.01 PO4@NC exhibits excellent rate performance, with a capacity of 111.2 mAh g at 10 C. -1 The discharge capacity.

[0025] Example 2 A preparation method of europium, antimony, niobium, Fe-coated and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material, the specific steps are as follows: (1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, and is placed in a 500° C. argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; (2) The obtained waste lithium iron phosphate positive electrode powder, lithium carbonate, ferric acetate, europium nitrate, antimony acetate, niobium hydroxide and ammonium dihydrogen phosphate were mixed in a molar ratio of 1:0.91:0.02:0.03:0.04:1, transferred to a plasma ball mill, and plasma ball milled in nitrogen to obtain a mixed precursor. The ball milling time was 90 min, the ball milling speed was 1100 r / min, the discharge frequency was 9 kHz, and the ball-to-material ratio was 20:1.

[0026] (3) The mixed precursor was placed in an argon tube furnace and calcined at a heating rate of 2°C / min, a calcination temperature of 750°C, and a treatment time of 5 h. Finally, the Eu-Sb-Nb Fe-co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material (LiFe 0.91 Eu 0.02 Sb 0.03 Nb 0.04 PO4@NC).

[0027] Figure 5 The regenerated lithium iron phosphate cathode material (LiFe) modified by waste lithium iron phosphate (SLFP) and Eu-Sb-Nb Fe co-doping and nitrogen-doped carbon coating 0.91 Eu 0.02 Sb 0.03 Nb 0.04 PO4@NC). It can be seen from the figure that SLFP has FePO4 impurity peaks, while LiFe 0.91 Eu 0.02 Sb 0.03 Nb 0.04 The PO4@NC material has consistent standard diffraction peaks with those of lithium iron phosphate (PDF#81-1173), indicating that the crystal structure of waste lithium iron phosphate is repaired and doping has no effect on the crystal structure of lithium iron phosphate.

[0028] Figure 6 LiFe 0.91 Eu 0.02 Sb 0.03 Nb 0.04 Cycling performance diagram of PO4@NC material at 1 C current density, with an initial discharge capacity of 157.9 mAh g -1 , the capacity retention rate is 96.3% after 200 cycles.

[0029] Example 3 A preparation method of europium, antimony, niobium, Fe-coated and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material, the specific steps are as follows: (1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, and is placed in a 500° C. argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; (2) The obtained waste lithium iron phosphate positive electrode powder, lithium carbonate, ferric acetate, europium nitrate, antimony acetate, niobium hydroxide and ammonium dihydrogen phosphate were mixed in a molar ratio of 1:0.925:0.05:0.005:0.02:1, transferred to a plasma ball mill, and plasma ball milled in nitrogen to obtain a mixed precursor. The ball milling time was 180 min, the ball milling speed was 1200 r / min, the discharge frequency was 10 kHz, and the ball-to-material ratio was 30:1.

[0030] (3) The mixed precursor was placed in an argon tube furnace and calcined at a heating rate of 10°C / min, a calcination temperature of 650°C, and a treatment time of 3 h. Finally, the Eu-Sb-Nb Fe-co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material (LiFe 0.925 Eu 0.05 Sb 0.005 Nb 0.02 PO4@NC).

[0031] Figure 7 Waste lithium iron phosphate (SLFP) and Eu-Sb-Nb co-doping and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate cathode material (LiFe 0.925 Eu 0.05 Sb 0.005 Nb 0.02 PO4@NC). It can be seen from the figure that SLFP has FePO4 impurity peaks, while LiFe 0.925 Eu 0.05 Sb 0.005 Nb 0.02 The PO4@NC material has consistent standard diffraction peaks with those of lithium iron phosphate (PDF#81-1173), indicating that the crystal structure of waste lithium iron phosphate is repaired and doping has no effect on the crystal structure of lithium iron phosphate.

[0032] Figure 8 LiFe 0.925 Eu 0.05 Sb 0.005 Nb 0.02 Cycling performance diagram of PO4@NC material at 1 C current density, with an initial discharge capacity of 153.4 mAh g -1 , the capacity retention rate is 99.7% after 200 cycles.

[0033] Comparative Example 1 The difference between this comparative example and Example 1 is that nitrogen doping is not used. The specific steps are as follows: (1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, and is placed in a 500° C. argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; (2) The obtained waste lithium iron phosphate positive electrode powder, lithium carbonate, ferric acetate, europium nitrate, antimony acetate, niobium hydroxide and ammonium dihydrogen phosphate were mixed in a molar ratio of 1:0.97:0.01:0.01:0.01:1, transferred to a plasma ball mill, and plasma ball milled in argon gas. The ball milling time was 60 min, the ball milling speed was 1300 r / min, the discharge frequency was 10 kHz, and the ball-to-material ratio was 10:1.

[0034] (3) The mixed precursor was placed in an argon tube furnace and calcined at a heating rate of 5°C / min, a calcination temperature of 700°C, and a treatment time of 6 h. Finally, the modified regenerated lithium iron phosphate positive electrode material (LiFe 0.97 Eu 0.01 Sb 0.01 Nb 0.01 PO4).

[0035] Fig. 9 For LiFe 0.97 Eu 0.01 Sb 0.01 Nb 0.01 PO4) material at 1 C current density. It can be seen from the figure that the discharge capacity is 149.9 mAh g -1 , the capacity retention rate after 200 cycles is 99.0%. By comparing Example 1 with Comparative Example 1, it can be found that nitrogen doping affects the performance of lithium iron phosphate. Without nitrogen doping, the conductivity of the prepared material will decrease, thereby reducing the energy density and power density of the battery. 0.97 Eu 0.01 Sb 0.01 Nb 0.01 The discharge specific capacity of the PO4 material is lower than that of Example 1.

[0036] Comparative Example 2 The difference between this comparative example and Example 1 is that nitrogen and niobium doping are not used. The specific steps are as follows: (1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, and is placed in a 500° C. argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; (2) The obtained waste lithium iron phosphate positive electrode powder, lithium carbonate, ferric acetate, europium nitrate, antimony acetate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1:0.98:0.01:0.01:1, transferred to a plasma ball mill, and plasma ball milled in argon gas. The ball milling time was 60 min, the ball milling speed was 1300 r / min, the discharge frequency was 10 kHz, and the ball-to-material ratio was 10:1.

[0037] (3) The mixed precursor was placed in an argon tube furnace and calcined at a heating rate of 5°C / min, a calcination temperature of 700°C, and a treatment time of 6 h. Finally, the modified regenerated lithium iron phosphate positive electrode material (LiFe 0.98 Eu 0.01 Sb 0.01 PO4).

[0038] Fig.10 For LiFe 0.98 Eu 0.01 Sb 0.01 PO4) material at 1 C current density. It can be seen from the figure that the discharge capacity is 144.5 mAh g -1 , after 200 cycles, the capacity retention rate was 95.7%. By comparing Example 1 with Comparative Example 2, it can be found that nitrogen and niobium doping will affect the performance of lithium iron phosphate. Without nitrogen and niobium doping, the conductivity of the prepared material will decrease, thereby reducing the energy density and power density of the battery, and increasing the binding energy between lithium atoms and oxygen atoms, resulting in a slow diffusion rate of lithium ions in the battery material. 0.98 Eu 0.01 Sb 0.01 The discharge specific capacity and capacity retention rate of the PO4 material are lower than those of Example 1.

[0039] Comparative Example 3 The difference between this comparative example and Example 1 is that only europium doping is used. The specific steps are as follows: (1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, and is placed in a 500° C. argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; (2) The obtained waste lithium iron phosphate positive electrode powder, lithium carbonate, ferric acetate, europium nitrate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1:0.99:0.01:1, transferred to a plasma ball mill, and plasma ball milled in argon gas. The ball milling time was 60 min, the ball milling speed was 1300 r / min, the discharge frequency was 10 kHz, and the ball-to-material ratio was 10:1.

[0040] (3) The mixed precursor was placed in an argon tube furnace and calcined at a heating rate of 5°C / min, a calcination temperature of 700°C, and a treatment time of 6 h. Finally, the europium-doped modified regenerated lithium iron phosphate positive electrode material (LiFe 0.99 Eu 0.01 PO4).

[0041] Fig.11 For using only europium doping (LiFe 0.99 Eu 0.01 PO4) material at 1 C current density, with a discharge capacity of 141.6 mAh g -1, after 200 cycles, the capacity retention rate was 84.6%. By comparing Example 1 with Comparative Example 3, nitrogen and niobium doping will affect the performance of lithium iron phosphate. Without nitrogen, niobium and antimony doping, the conductivity of the prepared material will decrease, thereby reducing the energy density and power density of the battery, increasing the binding energy between lithium atoms and oxygen atoms, slowing down the diffusion rate of lithium ions in the battery material, and reducing the structural stability of the lithium iron phosphate material during the charge and discharge process, shortening the service life of the battery, and the prepared LiFe 0.99 Eu 0.01 The discharge specific capacity and capacity retention rate of the PO4 material are lower than those of Example 1.

Claims

1. A method for preparing a Europium, Antimony, and Niobium Fe-coated and nitrogen-doped carbon-coated modified recycled waste lithium iron phosphate positive electrode material, characterized in that: The chemical expression of the recycled waste lithium iron phosphate positive electrode material is LiFe 1-x-y-z Eu x Sb y Nb z PO4@NC; the molar ratio of lithium, iron, europium, antimony, niobium and phosphorus is 1:1-xyz: x:y:z:1, where x=0.01~0.05, y=0.005~0.03, z=0.005~0.05; The preparation method of the regenerated waste lithium iron phosphate positive electrode material is achieved by the following steps: 1) The waste lithium iron phosphate battery is discharged to separate the positive electrode sheet, and the waste lithium iron phosphate positive electrode powder is obtained after ultrasonic drying, which is placed in a 500°C argon atmosphere tube furnace for pretreatment to remove residual binder and electrolyte; 2) mixing the obtained waste lithium iron phosphate positive electrode powder, lithium source, iron source, phosphorus source, europium source, antimony source and niobium source, transferring the mixture to a plasma ball mill, and performing plasma ball milling in nitrogen to obtain a mixed precursor; 3) The mixed precursor is placed in a tube furnace and calcined to finally obtain a europium, antimony, niobium, Fe-site co-doped and nitrogen-doped carbon-coated modified regenerated lithium iron phosphate positive electrode material.

2. The method for preparing a Europium, Antimony, and Niobium Fe-coated and nitrogen-doped carbon-coated modified recycled waste lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 2), the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium acetate, and lithium oxalate.

3. The method for preparing a Europium, Antimony, and Niobium Fe-coated and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 2), the iron source is one or more of ferric oxide, ferric acetate, ferric nitrate, ferrous sulfate, and ferrous oxalate.

4. The method for preparing a Europium, Antimony, Niobium, Fe-coated and nitrogen-doped carbon-coated modified recycled waste lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 2), the phosphorus source is one or more of lithium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate.

5. The method for preparing a Europium, Antimony, and Niobium Fe-coated and nitrogen-doped carbon-coated modified recycled waste lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 2), the europium source is one or more of europium nitrate, europium oxalate, europium acetate, and europium phosphate.

6. The method for preparing a Europium, Antimony, and Niobium Fe-coated and nitrogen-doped carbon-coated modified recycled waste lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 2), the antimony source is one or more of antimony pentoxide, antimony acetate, and antimony trichloride.

7. The method for preparing a Europium, Antimony, and Niobium Fe-coated and nitrogen-doped carbon-coated modified recycled waste lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 2), the niobium source is one or more of niobium oxide, niobium oxalate and niobium hydroxide.

8. The method for preparing a Eu-Sb-Nb Fe-co-doped and nitrogen-doped carbon-coated modified regenerated waste lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 2), the plasma ball milling time is 30-180 min, the ball milling speed is 900-1300 r / min, the discharge frequency is 5-10 KHz, and the ball-to-material ratio is 5-30:

1.

9. The method for preparing a Europium, Antimony, Niobium, Fe-coated and nitrogen-doped carbon-coated modified recycled waste lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 3), argon or nitrogen is used as the inert gas in the tubular furnace for calcination, the heating rate of the tubular furnace is 2-10°C / min, the calcination temperature is 500-750°C, and the holding time is 3-6 h.